DIAGNOSTIC ACCURACY OF SARS-COV-2 ANTIGEN TEST IN THE PEDIATRIC POPULATION: SYSTEMATIC REVIEW - Stevenie, (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
The early identification and subsequent isolation of SARS-CoV-2 infected individuals are two of the most important methods for avoiding the COVID-19 population spread. It's possible that about forty percent of those infected with high viral loads won't show any symptoms at all. Asymptomatic individuals are thought to be responsible for roughly 40% to 45% of SARS-CoV-2 infections, and they are able to spread the virus to others for a lengthy period of time, maybe more than 14 days. Antigen testing has many benefits, including a low overall cost and a short turnaround time, which all contribute to its ability to rapidly detect infected individuals. Testing using RT-PCR should be investigated when it has been determined that symptomatic patients have a negative response to antigen testing and that asymptomatic individuals have a positive response to antigen testing. The quantities of the SARS-CoV-2 virus found in children are significantly lower than those found in adults. It is essential to take into consideration the fact that the Ct values of those who are symptomatic and those who are asymptomatic do not differ considerably from one another. Before these tests are widely used in either national or international prevention strategies, it is necessary to carry out additional large studies in order to evaluate the clinical utility of these tests in the community. This evaluation must be carried out in order to conduct additional large studies. Antigen tests are shown to have an accuracy that is very near to being perfect in this article. Despite the fact that the majority of nations adhere to the agreement that PCR testing is required in order to diagnose COVID-19.